The indigenismo of the peruvian aprista party : a reinterpretation - Davies, Thomas M. (Pontificia Universidad Católica del Perú. Fondo Editorial, 1978)
For over forty years, scholars studying Latin America and Peru have been bombarded with hundreds of books, pamphlets, broadsides, and articles supporting, condemning, or "explaining" the Alianza Popular Revolucionaria Americana (Apra). However, even a casual glance at the literature reveals that it is almost totally polarized between the fervent supporters of the party and its equally fervent detractors. Apra has been pictured by its admirers as a grass-roots lower- and middle- class reform movement designed to end foreign and oligarchical domination of the economy, to incorpora te the Indian mass in to national life, and to democratize the socio-political structure of the country. One United States scholar wrote: ''The Apristas have demonstrated the vigor of their ideas. Their slogan in 1966, just as it has been far over four decades, is 'Apra Sí, Comunismo No'. They continue, as always, teaching, organizing, and working for the Peru of their ideal-free, just, and happy".Critics of Apra have long characterized the party as being composed of communistic terrorists who desire not the betterment of Peruvian society, but rather its total destruction. One historian recently wrote that Apra sought "to tear down the whole Peruvian social, economic, and política! structure so as to replace it with one based exclusively on their own esoteric theories, rather than on a consensus of national opinion. They were in Peru fully as subversive an element as is the Communist Party toda y in the United States".
Volumen 1. Páginas 121-140
Keywords: Trato a los indígenas--Perú; https://purl.org/pe-repo/ocde/ford#6.01.01